A Compact Wide-Range Frequency and Bandwidth Reconfigurable Filter - Tian, Mingen; Long, Zhihe; Feng, Lijun; He, Leilei; Zhang, Tianliang (IEEE microwave and wireless components letters, 2022)
This letter proposes a wide-range reconfigurable bandpass filter (WRBPF) based on the cross-shape triple-mode resonator. Varactor diodes and switching diodes are utilized at the ends of the resonator and the positions of external coupling, which combines the two working modes of the low-frequency band and high-frequency band, greatly broaden the tunable range of the center frequency ( f_{0} ). When the 3-dB bandwidth of WRBPF is 180 MHz, f_{0} can be adjusted from 0.78 to 1.93 GHz, and the relative adjustment range is 84.9%. When f_{0} is 1.355 GHz, the absolute bandwidth can be adjusted from 110 to 950 MHz, and the relative bandwidth adjustment range is 8.1%-70.1%. Moreover, the circuit size of WRBPF is only 0.29\,\,λ g\,\,× 0.22\,\,λ g . The experimental results show that WRBPF has not only a simple structure but also an excellent performance.